Peran Kepemimpinan Kepala Desa Dimasa Pandemi di Desa Riding Panjang Kepulauan Bangka Belitung - Nyimas Atika; Muhammad Robbani (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to determine the leadership role of the village head during the pandemic in Riding Panjang Village, Bangka Belitung Islands Province. Meanwhile, the research method used is a qualitative research method where there are instruments, namely: observation, interviews, and documentation. From the results of the research on the Leadership Role of the Village Head during the Pandemic in Riding Panjang Village, Bangka Belitung Islands Province, they have carried out their duties well because Riding Panjang Village, Bangka Belitung Islands Province was appointed by the sub-district as a representative of the Belinyu sub-district (Riding Village, Riding Panjang Village, Bangka Belitung Islands Province) as